PENGARUH RELATED PARTY TRANSACTION TERHADAP TAX AVOIDANCE DENGAN VARIABEL MODERASI PENGUNGKAPAN TATA KELOLA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - Chindy Helfin, Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to obtain empirical evidence on the effect of related party transaction to tax avoidance with corporate governance disclosure as a moderating variable that listed in Indonesia Stok Exchange, with a total of 109 samples. This study uses secondary data which were tested using software SmartPLS 3,0. The result of this study  suggests  that  related  party  transaction  significantly  influence  tax  avoidance. However, corporate governance disclosure doesn’t moderate the effect of related party transaction on tax avoidance.